The adoption of an improved rice variety (MAC18), which has reached 25% of Bolivian rice farmers, contributes to the adoption of other technologies and the increase of productivity and market access - CGIAR Research Program on Rice (2021)
The Bioversity-CIAT Alliance and the Latin American Fund for Irrigated Rice (FLAR) have disseminated germplasm through local partners across Latin America, which has contributed to breeding hundreds of improved varieties now supporting rice production. Bolivia is no exception, where the main variety adopted (MAC 18) comes from the breeding programs of the Alliance and FLAR. Its adoption has been associated with a greater likelihood of adopting other high-productivity technologies and with increased smallholders rice sales .